Respuesta :
Answer:
[tex]\frac{d^2y}{dx^2} = \frac{-4}{3}[/tex]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Algebra I
- Factoring
Calculus
Implicit Differentiation
The derivative of a constant is equal to 0
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Product Rule: [tex]\frac{d}{dx} [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)[/tex]
Chain Rule: [tex]\frac{d}{dx}[f(g(x))] =f'(g(x)) \cdot g'(x)[/tex]
Quotient Rule: [tex]\frac{d}{dx} [\frac{f(x)}{g(x)} ]=\frac{g(x)f'(x)-g'(x)f(x)}{g^2(x)}[/tex]
Step-by-step explanation:
Step 1: Define
-y - 2x³ = y²
Rate of change of tangent line at point (-1, -2)
Step 2: Differentiate Pt. 1
Find 1st Derivative
- Implicit Differentiation [Basic Power Rule]: [tex]-y'-6x^2=2yy'[/tex]
- [Algebra] Isolate y' terms: [tex]-6x^2=2yy'+y'[/tex]
- [Algebra] Factor y': [tex]-6x^2=y'(2y+1)[/tex]
- [Algebra] Isolate y': [tex]\frac{-6x^2}{(2y+1)}=y'[/tex]
- [Algebra] Rewrite: [tex]y' = \frac{-6x^2}{(2y+1)}[/tex]
Step 3: Differentiate Pt. 2
Find 2nd Derivative
- Differentiate [Quotient Rule/Basic Power Rule]: [tex]y'' = \frac{-12x(2y+1)+6x^2(2y')}{(2y+1)^2}[/tex]
- [Derivative] Simplify: [tex]y'' = \frac{-24xy-12x+12x^2y'}{(2y+1)^2}[/tex]
- [Derivative] Back-Substitute y': [tex]y'' = \frac{-24xy-12x+12x^2(\frac{-6x^2}{2y+1} )}{(2y+1)^2}[/tex]
- [Derivative] Simplify: [tex]y'' = \frac{-24xy-12x-\frac{72x^4}{2y+1} }{(2y+1)^2}[/tex]
Step 4: Find Slope at Given Point
- [Algebra] Substitute in x and y: [tex]y''(-1,-2) = \frac{-24(-1)(-2)-12(-1)-\frac{72(-1)^4}{2(-2)+1} }{(2(-2)+1)^2}[/tex]
- [Pre-Algebra] Exponents: [tex]y''(-1,-2) = \frac{-24(-1)(-2)-12(-1)-\frac{72(1)}{2(-2)+1} }{(2(-2)+1)^2}[/tex]
- [Pre-Algebra] Multiply: [tex]y''(-1,-2) = \frac{-48+12-\frac{72}{-4+1} }{(-4+1)^2}[/tex]
- [Pre-Algebra] Add: [tex]y''(-1,-2) = \frac{-36-\frac{72}{-3} }{(-3)^2}[/tex]
- [Pre-Algebra] Exponents: [tex]y''(-1,-2) = \frac{-36-\frac{72}{-3} }{9}[/tex]
- [Pre-Algebra] Divide: [tex]y''(-1,-2) = \frac{-36+24 }{9}[/tex]
- [Pre-Algebra] Add: [tex]y''(-1,-2) = \frac{-12}{9}[/tex]
- [Pre-Algebra] Simplify: [tex]y''(-1,-2) = \frac{-4}{3}[/tex]